LENDING PRACTICES AND SPECIFIC ASPECTS IN DEVELOPING COUNTRIES (World Economics and Finance Bulletin, 2024)
The article analyzes the characteristics and problems of lending practices in developing countries. The efficiency of the lending process affects economic growth and financial stability. In developing countries, the lending mechanism is mainly based on the relationship between the public and private sectors. In addition, types of lending, interest rates, credit risk and financial regulatory mechanisms are also discussed. The article also provides suggestions for improving lending in developing countries based on the experiences of developed countries.